2009
DOI: 10.1016/j.seizure.2009.04.007
|View full text |Cite
|
Sign up to set email alerts
|

FLIP&FLAP—A training programme for children and adolescents with epilepsy, and their parents

Abstract: FLIP&FLAP is an effective child- and family-centred programme. It is currently being established in Northern Germany to test its usefulness in routine care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
60
0
9

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(71 citation statements)
references
References 28 publications
2
60
0
9
Order By: Relevance
“…This somewhat disappointing result may indicate that increases in subjective QoL require major changes in social relationships, health status, or participation in new activities to alter self-perception of one's life having significantly improved. We note that one study found improvements in aspects of QoL, such as social exclusion, using a group intervention for CYPE [14]. It is, therefore, important to consider what type of intervention is likely to improve particular aspects of self-rated QoL, as health related QoL is a multi-faceted complex construct.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…This somewhat disappointing result may indicate that increases in subjective QoL require major changes in social relationships, health status, or participation in new activities to alter self-perception of one's life having significantly improved. We note that one study found improvements in aspects of QoL, such as social exclusion, using a group intervention for CYPE [14]. It is, therefore, important to consider what type of intervention is likely to improve particular aspects of self-rated QoL, as health related QoL is a multi-faceted complex construct.…”
Section: Discussionmentioning
confidence: 94%
“…This could be an important factor in improving friendship quality and participation in group activities. Many young people with epilepsy report feeling isolated from peers [6,14] and this can have an important developmental cost during adolescence -a period where young people typically engage as a group in behaviors associated with a level of risk as they navigate the increased levels of autonomy and independence available to them. The importance of participation in 'normal' group learning experiences and activities during adolescence offers key opportunities for personal growth, and social exclusion may be linked to later negative outcomes such as poorer quality of life (QoL) [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…40 These interventions aimed to increase medical knowledge about epilepsy, as well as educate families about the management of their children's symptoms. 40 Three studies reported a postintervention increase in parent and child knowledge [41][42][43] ; two resulted in improved family functioning 42 or parental anxiety 44 ; two reported no impact on level of caregiver depression or anxiety 43,45 ; and one was not evaluated. 46 Beyond educating parents about the management of their children's epilepsy, our findings suggest that the implementation and evaluation of family centered care practices that address caregiver well-being and provide linkages to supportive community resources may result in more promising HRQL for children and families.…”
Section: Discussionmentioning
confidence: 99%
“…국외에서는 간질아동을 대상으로 교육과 인지행동치료가 통합적 으로 제공된 중재 [9], 교육 중재 [10][11][12][13], 인지행동치료 [14], 운동중재 [15], 상담 [16] [7,20,21]. Bandura [22] Table 2).…”
unclassified